The reality of spinsterhood in the community of the city of Alamara, causes and solutions - Wisam A. Dargal ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The phenomenon of female spinsterhood is one of the social problems that spread in societies where wars abound and the economic, health and social reality deteriorates, especially in Arab societies in general and the study area in particular. The research aims to reveal the phenomenon of delayed female marriage in the city of Al-Amarah during the year (2021), and to know the demographic, economic and social characteristics of spinster females. Among the economic, social, health, personal and other reasons contributed to the males’ reluctance to marry and the rise of spinsterhood, and knowing the most important reasons for the delay in female marriage necessitated the development of solutions to them.